IL-17 and IL-22 in Cerebrospinal Fluid and Plasma Are Elevated in Guillain-Barré Syndrome - Shujuan Li; Ming Yu; Haifeng Li; Hongliang Zhang; Yanfang Jiang (Mediators of Inflammation)
Guillain-Barré syndrome (GBS) is an acute autoimmune-mediated inflammatory demyelinating disease that causes rapidly progressing paralysis and occasionally respiratory failure. We hypothesized that interleukin (IL)-17 and IL-22 are elevated in GBS and participate in the autoimmune inflammatory response of GBS. We used sandwich enzyme-linked immunosorbent assay (ELISA) to measure the IL-17 and IL-22 levels in the CSF, and plasma from 22 GBS patients at the acute phase and 18 healthy controls (HC). The results show that CSF and plasma levels of IL-17 and IL-22 are elevated in GBS patients compared with HC. IL-17 and IL-22 levels in CSF, respectively, are correlated with GBS disability scale scores (GDSs). Meanwhile, IL-17 and IL-22 levels in CSF, IL-22 in CSF, and plasma of GBS patients have positive correlation, respectively. The increased levels of IL-17 and IL-22 in CSF may be explained by the disruption of blood-brain barrier (BBB) and peripheral nervous system (PNS) local inflammation in GBS. Meanwhile, the elevated levels of these two cytokines in plasma suggest the activation of Th17 and Th22 cells in the systemic immune response of GBS. Our data provide preliminary evidence that GBS is associated with high levels of IL-17 and IL-22 in CSF and plasma. These cytokines display pathogenic potential and may serve as useful biomarkers for GBS.